2. Beitrag zur Kenntnis der Tineiden von Afghanistan (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1963)
As a result of the study of material recently collected by G. Ebert there is presented a second contribution towards the knowledge of Tineid Moths of Afghanistan, including descriptions of a new Infurcitinea-species and the female genitalia of Episcardia caerulipennis Ersch., and E. luteola Pet. Finally there are listed the 25 Tineid species which were found in this country up to now, with notes on their distribution and synonymy.Nomenclatural Actsbalchanella Zagulajev, 1956 (Cilicorneola), syn. n. of Fermocelina leucelloides (Amsel, 1935)nuristancia Petersen, 1963 (Infurcitinea), spec. n.straminella Zagulajev, 1958 (Monopis), syn. n. of Monopis christophi Petersen, 1957gracilis Gozmány, 1959 (Sphallestasis), syn. n. of Episcardia luteola Petersen, 1959distans Gozmány, 1959 (Tinea), syn. n. of Niditinea fuscipunctella (Haworth, 1828)